Refinement of the ISO 9126 model for evaluating software product quality in e-Book - N. N., Haslinda; M. A. Z., Fariha; A. W. S., Fahmy; W. O. W., Roslina; A. A. N., Sukinah; Y., Azliza; S. N., Suhana; Shiratuddin, Norshuhada (INSInet Publications, 2014)
Despite the widespread use of e-Book in education, there is yet a standard framework for evaluating the quality of software products in e-Book.Research efforts mainly focus on technological breakthroughs and limited to attention has been given to the evaluation of software product quality.As such, this paper aims to propose a refinement of the ISO 9126 model for evaluating software product quality in e-Book.Popular Software Quality Models are reviewed including McCall, Boehm, FURPS, Dromey and ISO 9126.Refinements to ISO 9126 resulted in the identification of five quality characteristics (Functionality, Reliability, Usability, Efficiency,Portability) and 16 sub -characteristics (Suitability, Accurateness, Security, Interoperability, Maturity, Fault Tolerance, Recoverability, Understandability, Learnability, Operability, Attractiveness, Time Behavior, Adaptability, Installability, Coexistence, Replaceability).There are two contributions of this work: a Software Quality Model for e-Book; and the identification of quality metrics to support the evaluation of software product. The refined model provides a formal method for evaluating software product quality in e- Book and the quality metrics serves as a foundation for the development of survey instruments and computer support system. It is hoped that this work would spark interest for the development of better e- Book applications.